2002
DOI: 10.1038/sj.hdy.6800140
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of maternal effect QTL to genetic architecture of early growth in mice

Abstract: Existing approaches to characterizing quantitative trait loci (QTL) utilize a paradigm explicitly focused on the direct effects of genes, where phenotypic variation among individuals is mapped onto genetic variation of those individuals. For many characters, however, the genotype of the mother via its maternal effect accounts for a considerable portion of the genetically based variation in progeny phenotypes. Thus the focus on direct effect QTL may result in an insufficient or misleading characterization of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 39 publications
4
65
0
Order By: Relevance
“…This maternal effect gene was identified by determining weights of F3 pups cared for by F2 mothers, when half the pups for each female were fostered and half were left with their biological mother. 24 The results demonstrated that maternal effect genes have significant effects on growth and that one of these QTLs is included within the B6.C-H1 congenic strain. We also cannot distinguish between the possibilities that imprinted genes or nonimprinted genes expression in mothers underlies the apparent maternal effect.…”
Section: Discussionmentioning
confidence: 86%
“…This maternal effect gene was identified by determining weights of F3 pups cared for by F2 mothers, when half the pups for each female were fostered and half were left with their biological mother. 24 The results demonstrated that maternal effect genes have significant effects on growth and that one of these QTLs is included within the B6.C-H1 congenic strain. We also cannot distinguish between the possibilities that imprinted genes or nonimprinted genes expression in mothers underlies the apparent maternal effect.…”
Section: Discussionmentioning
confidence: 86%
“…The F 2 males and females were then randomly mated to produce 200 full-sibling F 3 families with a total of 1,632 F3 animals. One hundred fifty-eight of the 200 F 3 families participated in a cross-fostering protocol in which half of the pups from a pair of litters born on the same day were reciprocally exchanged between mothers (43,45). Thus, for approximately half of the population of pups, the normal correlation between postnatal maternal and offspring genotypes was negated.…”
Section: Methodsmentioning
confidence: 99%
“…No interaction between genetic background and effect size was detected regardless of whether the untransformed data were analysed (yielding the absolute effect size in grams) or whether the data were first scaled to the within-line variation (yielding an estimate in phenotypic standard deviation units). Evidence of epistasis is found frequently in genome-wide QTL analyses of body size [1,17,24,30] although in most cases not all QTL are involved in epistatic interactions (but see [5]). The lack of interaction between genetic background and the QTL identified in this study may indicate that this particular QTL does not participate in epistatic interactions with other loci, or that its interactions with a number of loci negate each other.…”
Section: Discussionmentioning
confidence: 99%
“…However, it would be expected that the effects of QTL would depend on the genetic background, given that the expressivity, penetrance and dominance of Mendelian mutations are frequently found to be affected by modifier genes [22]. Although a number of studies have found evidence of epistasis between QTL or marker loci (e.g., [1,5,17,24,30]), the statistical power to detect epistasis is generally very low [20] making it difficult to study specific interactions [24,30]. An alternative to examining pair-wise interactions between loci in a mapping population is to focus on a single QTL and to introgress the QTL alleles into different genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%